Peran Keluarga Inti Sebagai Hakam Dalam Penyelesaian Syiqaq Perspektif Maqashid Syariah (Studi Kasus Desa Cempa) - Yunita Wati; Azhar (Peduli Riset dan Pengabdian Masyarakat, 2024)
This research is motivated by the occurrence of syiqaq in Cempa Village which was resolved non-litigation by the nuclear family who became the peacemaker (hakam). There are three points that are the focus of this problem, with the aim of knowing the factors causing syiqaq in Cempa Village, then the role of the nuclear family as hakam in resolving syiqaq in Cempa Village and a review of maqashid sharia in resolving syiqaq according to the MUI of Langkat Regency. This research was conducted using a field research method with a qualitative approach. The data were obtained using interview, observation, and documentation techniques. Data analysis using a descriptive method. The conclusion of this study is that the way the nuclear family resolves syiqaq in Cempa Village, Hinai District is by calling both husband and wife who experience syiqaq, then providing positive views and advice so that they do not continue their intention to divorce. Therefore, it is very necessary to have the right resolution and solution by reminding couples and families who are in polemics and feuds not to forget the pure purpose of a marriage, which includes creating a family that is sakinah, mawaddah, and Rahmah as the benefits of a marriage. And eliminating various things that cause harm that can result in harming and destroying a marriage.